Administrative structure and functions of drug regulatory authorities in India - Nupur Chowdhury; Pallavi Joshi; Arpita Patnaik; Arpita Saraswathy (Indian Council for Research on International Economic Relations (ICRIER), 2015)
Drug Regulation has been the focus of several recent policy reform efforts in India, starting with the Mashelkar Committee Report in 2003 to the most recent report of the Ranjit Roy Chaudhary Committee in 2013. Nevertheless, the regulatory structure continues to be plagued with several structural challenges, including issues related to regulatory harmonisation between the centre and the states, access to regulatory resources, transparency, which have undermined the general effectiveness of the regulatory system. At the juncture when the Drugs and Cosmetics (Amendment) Bill, 2015 to amend the Drugs and Cosmetic Act, 1940, is expected to overhaul the drug regulation, this study, the first of its kind, evaluates the administrative structure and functions of drug regulatory authorities at both the federal and state level along with comparative perspectives on similar challenges from other international jurisdictions. Through legal and policy analysis, supported by stakeholder interactions, this study not only provides a systematic analysis of the current challenges, along with actionable policy recommendations and suggests possible means for their operationalisation.
Keywords: I18; K32; K42; 330; Government Policy; Regulation; Public Health; Environmental; Health; Safety Law; Illegal Behaviour and the Enforcement of Law